3D reconstruction of elastin fibres in coronary adventitia. (6th September 2016) - LUO, T.; CHEN, H.; KASSAB, G.S.
Summary: A 3D reconstruction of individual fibres in vascular tissue is necessary to understand the microstructure properties of the vessel wall.  The objective of this study is to determine the 3D microstructure of elastin fibres in the adventitia of coronary arteries.  Quantification of fibre geometry is challenging due to the complex interwoven structure of the fibres.  In particular, accurate linking of gaps remains a significant challenge, and complex features such as long gaps and interwoven fibres have not been adequately addressed by current fibre reconstruction algorithms.  We use a novel line Laplacian deformation method, which better deals with fibre shape uncertainty to reconstruct elastin fibres in the coronary adventitia of five swine. A cost function, based on entropy and Euler Spiral, was used in the shortest path search. We find that mean diameter of elastin fibres is 1.67 ± 1.42 μ m and fibre orientation is clustered around two major angles of 8.9˚ and 81.8˚.  Comparing with CT‐FIRE, we find that our method gives more accurate estimation of fibre width.  To our knowledge, the measurements obtained using our algorithm represent the first investigation focused on the reconstruction of full elastin fibre length.  Our data provide a foundation for a 3D microstructural model of the coronary adventitia to elucidate the structure–function relationship of elastin fibres.